METAFISIKA KETUHANAN DALAM PANDANGAN KALAM DAN PENGALAMAN RELIGIUS - Iskandar Zulkarnain (UIN Sunan Kalijaga Yogyakarta, 2016)
Kalam, in general, could be stated as a study that focused to examine the central theological doctrines. By studying Kalam, it will give someone convictions based on solid arguments, not easily distracting by the change of time. Theological metaphysics is one of subject matter in Kalam. Metaphysics in Kalam supposed a certain level of understanding towards